1997
DOI: 10.1037/0012-1649.33.3.468
|View full text |Cite
|
Sign up to set email alerts
|

Changing relations between phonological processing abilities and word-level reading as children develop from beginning to skilled readers: A 5-year longitudinal study.

Abstract: Relations between phonological processing abilities and word-level reading skills were examined in a longitudinal correlational study of 216 children. Phonological processing abilities, word-level reading skills, and vocabulary were assessed annually from kindergarten through 4th grade, as the children developed from beginning to skilled readers. Individual differences in phonological awareness were related to subsequent individual differences in word-level reading for every time period examined. Individual di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

71
730
11
38

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 787 publications
(858 citation statements)
references
References 48 publications
71
730
11
38
Order By: Relevance
“…In typically developing samples of children, scores on complex memory tasks predict reading achievement independently of measures of phonological shortterm memory (e.g., Swanson, 2003;Swanson & Howell, 2001). Current evidence suggests that although phonological short-term memory is significantly associated with reading achievements over the early years of reading instruction, its role is as part of a general phonological processing construct related to reading development rather than representing a causal factor per se (Wagner et al, 1997;Wagner & Muse, in press). It is also well established that children with reading disabilities show significant and marked decrements on working memory tasks relative to typically developing individuals (Siegel & Ryan, 1989;Swanson, 1994Swanson, , 1999Swanson, Ashbaker, & Lee, 1996).…”
Section: Working Memory In Children With Reading Disabilitiesmentioning
confidence: 99%
“…In typically developing samples of children, scores on complex memory tasks predict reading achievement independently of measures of phonological shortterm memory (e.g., Swanson, 2003;Swanson & Howell, 2001). Current evidence suggests that although phonological short-term memory is significantly associated with reading achievements over the early years of reading instruction, its role is as part of a general phonological processing construct related to reading development rather than representing a causal factor per se (Wagner et al, 1997;Wagner & Muse, in press). It is also well established that children with reading disabilities show significant and marked decrements on working memory tasks relative to typically developing individuals (Siegel & Ryan, 1989;Swanson, 1994Swanson, , 1999Swanson, Ashbaker, & Lee, 1996).…”
Section: Working Memory In Children With Reading Disabilitiesmentioning
confidence: 99%
“…Empirical evidence for this has come from the fact that preliterate children who have better PA skills are in turn quicker to learn to read (Wagner & Torgesen, 1987), and that both the absolute level (Share, Jorm, MacLean, & Mathews, 1984) and rate of acquisition (Byrne, Fielding-Barnesley, & Ashley, 2000) of early PA skills are excellent predictors of elementary reading skills. Wagner et al (1997) found that individual differences in PA persisted in explaining reading abilities each year from kindergarten through fourth grade, whereas the relationships between reading and other skills faded with development. In fact, kindergarten PA is a better predictor of teenage reading ability than is kindergarten reading skill (MacDonald & Cornwall, 1995).…”
mentioning
confidence: 91%
“…For reading acquisition in alphabetic writing systems, preliminary awareness of the sound structure of oral language is beneficial (Bradley and Bryant, 1983;West and Stanovich, 1986). Children with dyslexia have difficulties or even miss to develop phonological awareness (Shaywitz and Shaywitz, 2005;Wagner and Torgesen, 1987;Wagner et al, 1997). They often struggle from the very start when learning the alphabetic principles that involve knowledge of grapheme-phoneme correspondences, which initialize the emergence of print sensitive brain networks (Brem et al, 2010) and, in turn, critically affect reading accuracy and speed as well as spelling and writing (Ehri, 1998;Snowling, 2000).…”
Section: Introductionmentioning
confidence: 99%